2021
DOI: 10.3389/fpsyt.2021.649399
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Healthcare Provision for Attention-Deficit/Hyperactivity Disorder in the United Kingdom: A Consensus Statement

Abstract: Background: Despite evidence-based national guidelines for ADHD in the United Kingdom (UK), ADHD is under-identified, under-diagnosed, and under-treated. Many seeking help for ADHD face prejudice, long waiting lists, and patchy or unavailable services, and are turning to service-user support groups and/or private healthcare for help.Methods: A group of UK experts representing clinical and healthcare providers from public and private healthcare, academia, ADHD patient groups, educational, and occupational speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 91 publications
2
91
0
1
Order By: Relevance
“…However, participants did not provide evidence of a clinical diagnosis. This was to facilitate participation from adults who self‐identify as having ADHD but who may not yet have a diagnosis or opted not to pursue a formal diagnosis, due to significant waiting lists and barriers to ADHD care 68–70 . Research has indicated that college students who self‐identify as having ADHD but are undiagnosed demonstrate more neuropsychological impairment than non‐ADHD peers, 71 which may possibly support the validity of self‐diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, participants did not provide evidence of a clinical diagnosis. This was to facilitate participation from adults who self‐identify as having ADHD but who may not yet have a diagnosis or opted not to pursue a formal diagnosis, due to significant waiting lists and barriers to ADHD care 68–70 . Research has indicated that college students who self‐identify as having ADHD but are undiagnosed demonstrate more neuropsychological impairment than non‐ADHD peers, 71 which may possibly support the validity of self‐diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This was to facilitate participation from adults who self‐identify as having ADHD but who may not yet have a diagnosis or opted not to pursue a formal diagnosis, due to significant waiting lists and barriers to ADHD care. 68 , 69 , 70 Research has indicated that college students who self‐identify as having ADHD but are undiagnosed demonstrate more neuropsychological impairment than non‐ADHD peers, 71 which may possibly support the validity of self‐diagnosis. However, we did not collect data on which participants self‐diagnosed and were formally diagnosed and could not analyse any significant differences between these groups or their frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that the coexistence of a diagnosis of ODD/CD, learning difficulties, anxiety, younger age, family dysfunction, and socioeconomic adversity were all risk factors for predicting poor treatment efficacy for ADHD[ 43 ]. This pathway analysis further focused on children with ADHD with ODD, and aggression led to poor treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Widely cited studies estimate the prevalence of adult ADHD in the general population to be 3-5% (9)(10)(11), with rates typically being higher for men, though concerns about overdiagnosis should be noted (5,(12)(13)(14). Increasing awareness and discussion about ADHD has led to development of several consensus and guidance documents internationally (15)(16)(17)(18)(19)(20)(21). In incarcerated populations, rates are thought to be disproportionately high (22), but underdiagnosed (23), leading to lobbying for prioritization of ADHD in prisons and calls for effective screening and treatment protocols (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%